“A most industrious and far-seeing Mohawk scholar”: Charles A. Cooke (Thawennensere), Civil Servant, Amateur Anthropologist, Performer, and Writer - Edwards, Brendan (Ontario History)

(untitled) (The Ontario Historical Society, 2010)
Charles Angus Cooke (Thawennensere) (1870-1958) was an Aboriginal artist and writer and a federal civil servant who, by attempting to establish a library and publish a Mohawk newspaper and dictionary, and by his recruitment of Native soldiers in World War I, tried to bring the knowledge and ideas of Native people into the educational and political realm of the Department of Indian Affairs. Cooke sought to redefine the Western medium of the printed word for the social, cultural and political benefit of Aboriginal peoples, without compromising Aboriginal cultural interests and beliefs. He was motivated by a sincere interest in protecting, strengthening, and promoting Aboriginal languages, histories, and cultural practices, and desire to create an environment where Aboriginal people could make meaningful contributions to Canadian political affairs.